Physical education and sports and their relationship to psychological anxiety among students in the secondary stage, the state of Annaba as a model - Saad, HADJADJ (The journal of contemporary issues in business and government, 2023)
We dealt with a topic entitled: Physical education and sports and its relationship to psychological anxiety in an important stage of the student’s life, which is the secondary stage, which would increase the severity of general anxiety in adolescents, and the general goal is the importance that physical education and sports provide in reducing their psychological anxiety, and the descriptive approach was used using the questionnaire tool, as it represented the original community withdrawn from the sample and the community of our research was the students of the baccalaureate, estimated at 1175 students. Taken from high schools in the state of Annaba, the sample was also randomly selected because it gives equal opportunities to all members of society, at the level of secondary schools of the municipality of Hajjar, Annaba state, and the number of forms distributed reached 336, but only 308 forms were accepted, because the rest 13 forms were canceled and 15 did not get them, it was found from the analysis of the results obtained in this study that physical education and sports have an impact on reducing the percentage of psychological anxiety among baccalaureate students during the class and outside its times, so it must be known that the physical education share Mathematics has a role in alleviating psychological anxiety among baccalaureate students.